Ion Beam Applications (IntechOpen, 2023)
Ion beam of various energies is a standard research tool in many areas of science, from basic physics to diverse areas in space science and technology, device fabrications, materials science, environment science, and medical sciences. It is an advance and versatile tool to frequently discover applications across a broad range of disciplines and fields. Moreover, scientists are continuously improving the ion beam sources and accelerators to explore ion beam at the forefront of scientific endeavours. This book provides a glance view on MeV ion beam applications, focused ion beam generation and its applications as well as practical applications of ion implantation.